The Use Of Deixis In Students’ Speech Text At Ma’had Sunan Ampel Al-Aly Dormitory Universitas Islam Negeri Malang - Nadiyatul Uswatul Hasanah; Januariyus Mujianto; Dwi Rukmini (EDUTEC : Journal of Education And Technology, 2021)
Through in the finding product of speech text, students’ can speech their knowledge, thoughts, and feeling to the listener. Deixis is one of parts in pragmatics. Deixis is parts hold intimate relation between textual meaning and context. And one of the speech text components that have to be show by the students’ to communicate the meaning in speech text. This study aimed at identifying the use of deixis in the students’ speech text at Ma’had Sunan Ampel Al-Aly Dormitory Universities Islam Negeri Malang and focus on how they realized in different texts. Descriptive qualitative method is used in this research. Eight research texts were chosen as the sample for analysis. The result shows that the speech text use all kinds of deixis, the use of person deixis is more dominant. Because the position of the speaker as the main characters is themselves of their own knowledge. The proximal form is more dominant rather than the distal form in the place deixis. In the time deixis was used by present time, past time, and future time. In the social deixis was used in two parts. Therefore, absolute social deixis and relational social deixis. After that in the discourse deixis used through discourse marker and form of demonstrative this/that. Also, deixis is highly context-dependent that is cannot be understood without considering the context. Therefore, in realizing students' speech texts, English learners cannot only understand in the whole context of the students' speech text also trust on their vocabularies need. Because of this research for the future can improve knowledge of pragmatics especially in the speech text of deixis.